Does total tumour diameter, multifocality, number of tumour foci, or laterality predict lymph node metastasis or recurrence in differentiated thyroid cancer - YAVUZ, DİLEK (My University, 2023)
Introduction: Data regarding laterality, focality, or total tumour diameter (TTD) in papillary thyroid cancer (PTC) are limited. We aimed to investigate the impact of focality, TTD, number of tumour foci, or laterality on aggressive features in PTC. Material and methods: Patients were categorized based on maximum tumour diameter (MTD) (≤ 10 vs. > 10 mm), focality, laterality, or the number of tumour foci (1/2/ ≥3). We also categorized the patients as follows: Group 1, unifocal microcarcinoma (MTD ≤ 10/TTD ≤ 10 mm); Group 2, multifocal microcarcinoma (MTD ≤ 10/TTD ≤ 10 mm); Group 3, multifocal microcarcinoma (MTD ≤ 10/TTD > 10 mm); Group 4, unifocal macrocarcinoma (MTD > 10/TTD > 10 mm); Group 5, multifocal macrocarcinoma (MTD > 10/TTD > 10 mm). Results: The mean diagnosis age (n = 511) was 44.7 (± 12.7) years, the majority of the patients were < 55 years old (n = 310) and female (n = 416). An increasing number of tumour foci were associated with a higher MTD or TTD, a higher ratio of extrathyroidal extension (ETE), vascular or lymphatic invasion, lymph node metastasis (LNM) or distant metastasis, or the need for radioactive iodine (RAI). There was no difference in the parameters between Group 3 and Group 2, or Group 4. Vascular invasion, American Thyroid Association high risk, LNM at diagnosis, and RAI total dose were higher in Group 5 than in Group 3. Microscopic or macroscopic ETE, T1b, and T4a were positive predictors for recurrence. Male sex, multifocality, number of tumour foci (≥ 3), MTD (> 10 mm), TTD (> 10 mm), Group 5, microscopic or macroscopic ETE, lymphatic or vascular invasion, RAI need, T2, and T4b were positive predictors for LNM. Conclusion: MTD and TTD increase the risk of LNM but not the recurrence in PTC. TTD, multifocality, and bilaterality can be considered risk factors in PTC staging systems and risk calculators.
Keywords: thyroid; cancer; papillary; diameter; focality; laterality